The biomechanics of various fixations for syndesmotic joint diasthesis: a finite element study - Che Ahmad, Aminudin; Perwira, Marazuki; Abdul Rashid, Abdul Halim; Abdul Kadir, Mohammed Rafiq (2014)
Introduction Management of syndesmotic injury is very much open to debate. Controversies aroused in many aspects, and yet no single treatment is considered as gold standard. The surgical management is still evolving. Positional screw has been widely used as a stabilizer while waiting for healing but the utilization of screw itself is varied. Kirschner wire has been used for temporary stabilizer and the clinical results revealed good outcome. Interosseous suture has emerged as an alternative way in restoring syndesmotic joint function, also with good clinical outcome. We conduct a study to analyse the behaviour of all three implants used in the management of ankle syndesmosis diasthesis.